Alzheimer’s, music therapy & social work intervention - Cuadrado Cenzual, María Ángeles; Peláez Escribá de Balaguer, Gloria; Castillo Charfolet, Aurora (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This work aims to approaching the role of music therapy in relation to Alzheimer’s disease (AD) within the field of Social Work. In order to do that, a bibliographical revision is carried out and some key concepts, such as music therapy, Alzheimer Disease, or social work intervention, are selected. The information gathered leads to the conclusion that music therapy works as an adjuvant treatment for Alzheimer patients through areas such as social integration, self-esteem, communication, or stress reduction. Thus, it is concluded that musical stimulation improves AD patients’ quality of life.